Islam, youth and modernity in the Gambia : the Tablighi Jama{u1D20} - Janson, Marloes (New York : Cambridge University Press, 2014)
'This monograph deals with the sweeping emergence of the Tablighi Jama'at - a transnational Islamic missionary movement that has its origins in the reformist tradition that emerged in India in the mid-nineteenth century - in the Gambia in the past decade. It explores how a movement that originated in South Asia could appeal to the local Muslim population - youth and women in particular - in a West African setting. By recording the biographical narratives of five Gambian Tablighis, the book provides an understanding of the ambiguities and contradictions young people are confronted with in their (re)negotiation of Muslim identity. Together these narratives form a picture of how Gambian youth go about their lives within the framework of neoliberal reforms and renegotiated parameters informed by the Tablighi model of how to be a'true' Muslim, which is interpreted as a believer who is able to reconcile his or her faith with a modern lifestyle'--
'This monograph deals with the sweeping emergence of the Tablighi Jama'at - a transnational Islamic missionary movement that has its origins in the reformist tradition that emerged in India in the mid-nineteenth century - in the Gambia in the past decade. It explores how a movement that originated in South Asia could appeal to the local Muslim population - youth and women in particular - in a West African setting. By recording the biographical narratives of five Gambian Tablighis, the book provides an understanding of the ambiguities and contradictions young people are confronted with in their (re)negotiation of Muslim identity. Together these narratives form a picture of how Gambian youth go about their lives within the framework of neo-liberal reforms and renegotiated parameters informed by the Tablighi model of how to be a'true' Muslim, which is interpreted as a believer who is able to reconcile his or her faith with a modern lifestyle'--
Machine generated contents note: 1.'Life is a test, the hereafter is the best'; 2.'Welcome to the smiling coast': Muslim politics in the Gambia; 3. The global meeting the local: the Tablighi Jama'at contextualized; 4. Back to the ghetto; 5. A jihad for purity; 6. Learning to be a good Muslim woman; 7. Male wives and female husbands; 8. Hungry for knowledge; 9.'Muslims are sleeping and we have to wake them up'.
Includes bibliographical references and index.
Keywords: Tablighi Jama{u1D2E}; Islam -- Gambia; Islam -- Missions; Muslim youth -- Gambia; Youth movements -- Gambia